Values Of Character Education In The Finalist Short Story Collection At The Provincial Level Of The 2014 Fls2n - Edaroini, Edaroini; Missriani, Missriani; Wardiah, Dessy (Jurnal Pendidikan Tambusai, 2021)
The title of this article is “Values Of Character Education In The Finalist Short Story Collection At The Provincial Level Of The 2014 FLS2N” this discuss character education values. The goal of this research is to know to the education character values in the main character for the short story’s finalist provincial level FLS2N 2014. The benefits of this research can increase and adding to knowledge the study of literature especially short story through the character educations. Values practically this research hopes can give contribution for Indonesian language studies in schools. The method used is descriptive method. The source of the data in this reseach is the collect of short story’s finalist in provincial level FLS2N 2014 is Kejai Songket story by Agnes Twenty Agustiola, Melody Strains Sari story by Miranti Intan Alya, and Save Them for Us Father story by Purnama Djasmin. The data analysis technique used in content analysis technique. The result of this research is to show about character education among them relationships to one and only God such as religions, human relationships such as honesty, hard work, creative, independent, curiosity, partriotism, responsibility, love peace and relationship to the environment such as care for the environment.